Toward a Systemic Ethics of Public–Private Partnerships Related to Food and Health - Marks, Jonathan H. (Kennedy Institute of Ethics journal, 2014)
, Public–private partnerships have become widespread in the pursuit of both health-related research and public health interventions—most notably, in recent measures intended to address obesity. Participants emphasize synergies between the missions or goals of the public and private partners. However, the missions usually diverge in significant ways. Consequently, these partnerships can have serious implications for the integrity of, as well as trust and confidence in, the public partners. In this article, I highlight systemic concerns presented by public–private partnerships related to food and health. These include research agenda distortion and framing effects—not least, the characterization of obesity primarily as a question of individual behavior, and the minimization or neglect of the role of food systems and other social and environmental factors on health. Prevailing analytical approaches to public–private partnerships tend to downplay or ignore these systemic effects and their ethical implications. In this article, I offer guidance intended to help actors in the public sector fulfill their mission while thinking more critically and systemically about the ethical implications of public–private partnerships.